Analisis dan Perancangan Sistem Informasi Penjualan Water Meter Equipment Berbasis Web - Cecep Kurnia Sastradipraja; 1Rendy Said Kusmana (Jurnal Riset Sistem Informasi dan Teknologi Informasi (JURSISTEKNI), 2021)
The purpose of this research was to analyze and design a web-based sales information system at CV. Ryan Jaya Bandung, where the sales, purchasing, and stock systems are still done manually. With this process, data loss often occurs, the lack of supervisory control, and the length of the data input process. Data collection was carried out by using literature study techniques, observation, and interviews. The method used in the development of information systems uses a prototype model and system testing using blackbox testing. Based on the results of the research conducted to produce a web-based sales information system following user expectations, and the test results show that the system built is following user needs.